Mansour II, who is known as the owner of Hama. King - Ahmed, Ahmed S. (Humanities Journal of University of Zakho, 2018)
The main aim of the current study is give a picture of the life of King Mansour II, who is known as the owner of Hama. He was an Ayubid figure who appeared at a time when the Ayubid state was suffering from rupture and disintegration. The paper is divided into four sections. The first section tackled his personal life, his origins and everything related to his family. The second section dealt with his political life by giving a clear picture of his father, King Al-Muzaffar (626-642 AH/1229-1284 AD), who died when King Al-Mansour was young, and how he became under the tutelage of his mother and took power in Hama. The third section shed light on the internal political relations between the Ayubids. These relations were characterized by anxiety and lack of a clear political line due to the existence of conflicting interests. This was mainly related to the fact that the political future of the Ayubid family, their state, and conflict between the kings of the Ayubids in the Levant and Egypt were not clearly taken into consideration. Finally, the fourth section explained King Mansour’s relations with the new rulers of Egypt, the Mongols and Armenians, presenting his role in the battles of Ain Jalut and the Battle of Homs I and II.